α2δ-1–Bound NMDA Receptors Mediate Morphine-induced Hyperalgesia and Analgesic Tolerance by Potentiating Glutamatergic Input in Rodents - Deng, Meichun (Anesthesiology, 2019)
BACKGROUND: Chronic use of μ-opioid receptor agonists paradoxically causes both hyperalgesia and the loss of analgesic efficacy. Opioid treatment increases presynaptic N-Methyl-D-aspartate receptor (NMDAR) activity to potentiate nociceptive input to spinal dorsal horn neurons. However, the mechanism responsible for this opioid-induced activation of presynaptic NMDARs remains unclear. α2δ-1, formerly known as a calcium channel subunit, interacts with NMDARs and is primarily expressed at presynaptic terminals. In this study, we tested the hypothesis that α2δ-1–bound NMDARs contribute to presynaptic NMDAR hyperactivity associated with opioid-induced hyperalgesia and analgesic tolerance. METHODS: Rats (5 mg/kg) and wild-type and α2δ-1–knockout mice (10 mg/kg) were treated intraperitoneally with morphine twice/day for 8 consecutive days, and nociceptive thresholds were examined. Presynaptic NMDAR activity was recorded in spinal cord slices. Coimmunoprecipitation was performed to examine protein-protein interactions. RESULTS: Chronic morphine treatment in rats increased α2δ-1 protein amounts in the dorsal root ganglion and spinal cord. Chronic morphine exposure also increased the physical interaction between α2δ-1 and NMDARs by 1.5 ± 0.3 fold (mean ± SD, p = 0.009, n = 6) and the prevalence of α2δ-1–bound NMDARs at spinal cord synapses. Inhibiting α2δ-1 with gabapentin or genetic knockout of α2δ-1 abolished the increase in presynaptic NMDAR activity in the spinal dorsal horn induced by morphine treatment. Furthermore, uncoupling the α2δ-1–NMDAR interaction with an α2δ-1 C-terminus–interfering peptide fully reversed morphine-induced tonic activation of NMDARs at the central terminal of primary afferents. Finally, intraperitoneal injection of gabapentin or intrathecal injection of an α2δ-1 C-terminus–interfering peptide or α2δ-1 genetic knockout abolished the mechanical and thermal hyperalgesia induced by chronic morphine exposure and largely preserved morphine’s analgesic effect during 8 days of morphine treatment. CONCLUSIONS: α2δ-1–bound NMDARs contribute to opioid-induced hyperalgesia and tolerance by augmenting presynaptic NMDAR expression and activity at the spinal cord level.